(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study examines pictorial teaching strategy to improve reading comprehension challenges among primary school pupils in Ikere Local Government Area of Ekiti State. A descriptive survey design is adopted for the study with the selection of one hundred female and male teachers randomly drawn from urban and rural areas of the study area. The instrument used is a self-structured questionnaire of twenty items tagged ’ Pictorial Teaching Questionnaire’ (PTQ). The instrument is validated by experts in Curriculum Studies. Data collected are analyzed using simple percentages and mean. The results show that picture reading strategy is utilized by primary school teachers which have impacted positively on the reading comprehension abilities of pupils. The study recommends that pictorial teaching should be more encouraged to aid reading comprehension and that government should strive to assist indigent pupils to procure relevant texts. Curriculum planners should try to integrate more pictures into English texts most especially at the elementary stage of reading for pupils.